In-situ XRD vs ex-situ vacuum annealing of tantalum oxynitride thin films: Assessments on the structural evolution - Cunha, L. (2018)
The purpose of this work is to discuss the main structural characteristics of a group of tantalum oxynitride (TaNxOy) thin films, with different compositions, prepared by magnetron sputtering, and to interpret and compare the structural changes, by X-ray diffraction (XRD), when the samples are vacuum annealed under two different conditions: i) annealing, followed by ex-situ XRD: one sample of each deposition run was annealed at a different temperature, until a maximum of 800 ◦C, and the XRD patterns were obtained, at room temperature, after each annealing process; ii) annealing with in-situ XRD: the diffraction patterns are obtained, at certain temperatures, during the annealing process, using always the same sample. Insitu XRD annealing could be an interesting process to perform annealing, and analysing the evolution of the structure with the temperature, when compared to the classical process. A higher structural stability was observed in some of the samples, particularly on those with highest oxygen content, but also on the sample with non-metal (O + N) to metal (Ta) ratio around 0.5.